Microcatheter Navigation and Thrombolysis in Acute Symptomatic Cervical Internal Carotid Occlusion - Srinivasan, A.; Goyal, M.; Stys, P.; Sharma, M.; Lum, C. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: The treatment of acute stroke distal to an occluded cervical internal carotid artery (ICA) presents a challenge. We report our results of endovascular therapy in 7 patients presenting with acute symptomatic cervical ICA occlusion.PATIENTS AND TECHNIQUES: Among patients presenting with acute stroke at our institution from June 2001 to June 2005, we retrospectively identified 7 patients who underwent endovascular therapy of acute cervical ICA occlusion. The techniques used for vessel recanalization were analyzed. Postprocedure CT scans were reviewed for hemorrhage. The clinical outcomes were assessed by using the modified Rankin scale (mRS) with good outcomes assigned scores of ≤2.RESULTS: All 7 patients revealed cervical ICA occlusion, with additional intracranial thrombus in 6 of the 7 patients. In all patients, a guiding catheter was placed in the ipsilateral common carotid artery proximal to the occlusion and a microcatheter advanced through the ICA clot to deliver intra-arterial (IA) tissue plasminogen activator (in 6 patients, the microcatheter was also advanced intracranially for thrombolysis). Successful recanalization of the occluded ICA was achieved in 6 patients. In 3 patients, balloon angioplasty and stent placement of the cervical ICA was also performed. Follow-up CT in 6 patients showed small basal ganglia infarcts in 4, patchy parietal infarcts in one, and frontal lobe hematoma in one patient. At 1 month after the procedure, 5 patients had good clinical outcomes (mRS of 0 in 4 patients and 1 in one patient).CONCLUSION: Performance of IA thrombolysis by passing a microcatheter through an acutely occluded internal carotid artery may be an effective therapy in acute stroke.